1991
DOI: 10.1523/jneurosci.11-12-04003.1991
|View full text |Cite
|
Sign up to set email alerts
|

Myelin sheath survival following axonal degeneration in doubly myelinated nerve fibers

Abstract: Axonal contact plays a critical role in initiating myelin formation by Schwann cells. However, recent studies of “double myelination” have indicated that myelin maintenance continues in Schwann cells completely displaced from physical contact with the axon. This raises the possibility either that diffusible trophic factors are produced by the axon, or that the axon is not required for myelin maintenance by these displaced Schwann cells. To test these hypotheses, the axons involved in double myelination in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(42 reference statements)
0
9
1
Order By: Relevance
“…6A-C) strongly suggest an active wrapping process rather than secondary collagen ingrowth. Axon-independent myelination, as reported here, is also different from "double myelination" that can occasionally result from the displacement of one internode by the interposition of another myelinating Schwann cell (Kidd and Heath, 1991).…”
Section: "Remak Myelin"contrasting
confidence: 53%
“…6A-C) strongly suggest an active wrapping process rather than secondary collagen ingrowth. Axon-independent myelination, as reported here, is also different from "double myelination" that can occasionally result from the displacement of one internode by the interposition of another myelinating Schwann cell (Kidd and Heath, 1991).…”
Section: "Remak Myelin"contrasting
confidence: 53%
“…During Wallerian degeneration, Schwann cell responses are initiated by a positive signaling event that requires close contact with damaged axons (Kidd and Heath, 1991). Exposure to recombinant neuregulin in vitro can induce demyelination that mimics the early response of Schwann cells to nerve damage in animals .…”
Section: Discussionmentioning
confidence: 99%
“…Because Wallerian degeneration is initiated only within Schwann cells that contact the axon (Kidd and Heath, 1991), we used immunostaining techniques and deconvolving microscopy to determine the subcellular localization of erbB2 in myelinated axons. In teased nerve fiber preparations of rat sciatic nerve, we occasionally noted weak erbB2 immunostaining at the perinu- Early and late activation of erbB2 after axotomy.…”
Section: Receptor Tyrosine Kinases Are Localized To the Microvilli Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mammalian optic nerve, similar anomalies have been ascribed to degenerative processes [Cooke, 1974;Sturrock, 1987;Kidd and Heath, 1991], or to developmental accidents [Peters et al, 1976]; it is somewhat curious that these anomalies have not been described in the chelonian optic nerve [Geri et al, 1982;Woodbury and Ulinski, 1986]. Their presence in metamorphosing amphibians suggests that these anomalies might be related to some unidentified dynamic aspect of neuronal organization, and further studies are indicated to elucidate the question.…”
Section: Myelinationmentioning
confidence: 99%